Motif Hijrah Generasi Z: Studi Kasus Followers Tiktok @Hanan_Attaki_ - Kusumawati, Reni; Suseno, Ari; Riza Gusti Rahayu (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to explore the migration motives that underlie generation Z in following Ustadz Hanan Attaki's TikTok account. Alfred Schutz's phenomenological study was used as a theoretical framework to understand the motives and subjective experiences of the informants. The research method used was a qualitative approach by conducting in-depth interviews with 9 informants who were active viewers and followed Ustadz Hanan Attaki's TikTok account from generation Z. The data collected was then analyzed based on the concept of "because" motive and "goal" motive. " (motif in order) Schutz. The research results show that there are various migration motives behind generation Z in following Ustadz Hanan Attaki's TikTok account. The “because” motive includes past spiritual experiences, environmental influences, and identity crises. Meanwhile, the "goal" motive includes the desire to improve oneself, search for the meaning of life, and gain inner peace. These findings provide a deeper understanding of the dynamics of migration among generation Z in the digital era.